National identity and distrust in the police: the case of North West Wales - Machura, Stefan (European journal of criminology, 2019)
Trust in the police, as defined by perceived procedural fairness, just decisions and effectivity, may be impacted by deep political divisions among the population, especially where citizens adopt opposing national identities. In Europe, North West Wales is one such area. Nationalism is intensified by language issues (Welsh vs. English) and historical experiences of UK institutions. A sample of 207 residents living within the local authority of Gwynedd were asked to take part in the study. A questionnaire survey addressed how much trust in the police ultimately depends upon national identity as expressed by preference for the Welsh language, trust in UK institutions and attitudes towards political symbols. Other factors tested included personal experience of the police, the influence of news reports and police TV series, as well as the perceived effectiveness of the police in addressing crime. Trust in UK institutions, preference for the Welsh language and news reporting were found to have most influence on trust in the police.